Mothers' postpartum psychological adjustment and infantile colic - ÖZEK, EREN (BMJ PUBLISHING GROUP, 2006)
Background: Infantile colic is a common problem of early infancy. There is limited data on the relation between postpartum maternal psychological problems and colic. Aim: To investigate whether infantile colic is associated with postpartum mood disorders or insecure adult attachment style of the mother. Methods: Seventy eight mothers and newborns were enrolled in this prospective, longitudinal study. Maternal depressive symptoms were screened with Edinburgh Postpartum Depression Score ( EPDS) and maternal anxiety was assessed with State- Trait Anxiety Inventory ( STAI). The Adult Attachment Scale was used to determine the attachment style of the mother. Infantile colic was defined according to Wessel criteria. Results: Infantile colic was present in 17 infants ( 21.7%); 12.9% of the mothers had an EPDS >= 13. The mean EPDS of the mothers whose infants had infantile colic ( 10.2 +/- 6.0) was significantly higher than that of the mothers of infants without colic ( 6.3 +/- 4.0). Among infants with infantile colic, 62.5% had mothers who had insecure attachment style, whereas only 31.1% of mothers had insecure attachment when the infant did not have infantile colic. Conclusion: Postpartum maternal depressive symptoms and insecure attachment style are associated with infantile colic. Screening and early intervention of postpartum depression might promote the health of both the mother and infant.
Keywords: POSTNATAL DEPRESSION; RISK